Additive manufacturing as an essential element of industry 4.0 for the benefit of engineering: a bibliometric analysis - Díaz-Martínez, Marco Antonio (2024)
Additive manufacturing, fundamental in industry 4.0, transforms production by creating three-dimensional objects through successive layers. This technology offers design flexibility and material efficiency but faces challenges in optimizing processes to ensure quality and precision. Its integration with industry 4.0 presents issues such as CAD system interoperability, data management, and cybersecurity. Despite these challenges, it enables the creation of complex geometries, reduces raw material consumption, and improves the final product properties. Research into materials and processes is accelerating its adoption, fostering personalized, sustainable, and decentralized business models. This approach is revolutionizing industrial and domestic production and will reshape business models and product design. In the research, 257 documents were reviewed, 172 were excluded, and 85 texts were analyzed using MAXQDA v.2020 for bibliometric analysis.